(3GdfXGe GdbGfhfj ddYbO GdEdcJQhfj hGdeSFhdjI Yf GdGYJOGAGJ GdEdcJQhfjI (B:s (3OQGSI ebGQfI aj GdbhGfjf GdhWfjI hbGfhf GdChfSjJQGd GdfehPLj hGdabg GdESdGej (B/s - (3hgOGf, QVG eJhdjs ((3GdefUhQI, eUQ (B:s (3OGQ GdacQ hGdbGfhf ddfTQ hGdJhRjY,s, 2017)
(3jJfGhd cJGH (B((3GdfXGe GdbGfhfj ddYbO GdEdcJQhfj hGdeSFhdjI Yf GdGYJOGAGJ GdEdcJQhfjI(B) (3hGdPj bGe HJCdjag (B((3QVG eJhdj hgOGf(B) (3aj MhGdj (B(157) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3dYbhO GdEdcJQhfjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3eaGJjM GdOQGSI GdeHMK GdChd (B: (3CUhd GdGfYbGO GdEdcJQhfj, (B1. (3CQcGf GdYbO GdEdcJQhfj, (B2. (3GdEjLGH hGdbHhd aj GdYbO GdEdcJQhfj, (B3. (3eLdS GdYbO GdEdcJQhfj, (B4. (3EOQGL GdTQhW aj GdYbO GdEdcJQhfj, (B5. (3GSJXgGQ GdEQGOI GdeYjHI aj GdYbO GdEdcJQhfj GdeHMK GdKGfj (B: (3EKHGJ GdGfYbGO GdEdcJQhfj (B: 1. (3hSGFd GdEKHGJ GdEdcJQhfj, (B2. (3GdefGRYI aj GdEKHGJ, (B3. (3GdbGfhf GdhGLH GdJWHjb GdeSDhdjI Yf GdGYJOGAGJ GdEdcJQhfjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B151-154.s
Keywords: (3dLfI GdCee GdeJMOI ddbGfhf GdJLGQj GdOhdjs; (3GdYbhO GdEdcJQhfjIs -- (3bhGfjf hJTQjYGJs; (3GdYbhO GdEdcJQhfjI (B((3abg ESdGej(B)s